Rooting of Mini-Cuttings of guava cultivars (Psidium guajava L.) Treated with IBA under Misting Irrigation - Supanjani, Supanjani; Rahayu, Hatari; Suprijono, Eko; Romeida, Atra; Yulian, Yulian (Faculty of Agriculture, The University of Bengkulu, 2020)
Guava (Psidium guajava L.) is a plant whose fruit is very popular in Indonesia because it contains high vitamin C and its leaves can be used as herbal medicine. Orchard expansion of selected cultivars and fruit production of guava can be achieved vegetatively through propagation by using mini-cuttings with the use of Indole Butyric Acids (IBA). A study was conducted to compare rooting success of mini-cuttings of herbaceous stem of four guava cultivars with IBA treatment. Four guava cultivars tested were Bengkulu Round, Getas, Crystal, and Bangkok. Mini-cuttings were immersed in IBA solution at 0 ppm or 1000 ppm. Cultivar and IBA treatments were arranged factorially in a randomized complete block design with 3 replications, each consisting of 25 cuttings. Variables observed included percentage of original-leaf shedding, percentage of emerging shoots, percentage of sprouting cuttings, new leaf number, root number, root length, and percent of rooted cuttings. The results demonstrated that cultivars affected rooting percentage, sprouted percentage, percentage of original-leaf fall, and number of root. Getas had highest rooting and sprouting percentages, and showed lowest number of original-leaf shedding; whereas, Bangkok demostrated greatest number of root. IBA treatment increased the number of root and the number of original-leaf shedding, but reducing rooting percentage of mini-cutting. There was no interaction between cultivar and IBA teratment.